Working Women in Healthcare Services: between Wage Work and Domestic Work. - Mustapha LAHROUZ; Abdeladim ZEHANI; Badreddine DAHOU; Sara EL FELLAQ (African Scientific Journal, 2023)
Morocco’s efforts to promote women’s rights have succeeded in recent years to introduce important legislative reforms that serve the interests of women through increasing their socioeconomic status. Moroccan Constitution of 2011 enshrines the total equality of rights between men and women, including political and economic rights, in accordance with the international agreements to which Morocco has voluntarily approved. The perception of equality between all citizens is the main foundation of any true democratic and equal society. However, economic change through privatization of public sectors has had undesirable outcomes on working-class and lower middle-class women. Structural adjustments and economic liberalization were not followed by official assessments to evaluate its direct impact on female emancipation and gender equality. Contrarily, capitalism stressed gender inequality through covering women’s exploitation with libertarian features. The findings of this study confirmed that social roles are still distributed on gender basis. Although Moroccan women participate fully in the national economy, they still perform domestic chores in the same way and with the same intensity. Moroccan male mentality still considers domestic chores as women’s duty. As a result, the heavy burden of double task becomes the main cause of conflicts coming from private spheres. Unfortunately, the majority of participants revealed that they have a difficult and unstable life because of the limited support they receive at home.